Population growth and policy options in the developing world - Bongaarts, John; Bruce, Judith (International Food Policy Research Institute, 1998)
The population of the developing world has doubled since 1965 and now stands at 4.8 billion. This growth in human numbers has been a principal cause of a rising demand for food, water, and other life-sustaining resources in the past and will continue to be so for the foreseeable future. The authors examine the question of why massive further growth will take place despite declining fertility rates and identify a number of factors. Well-designed population policies are broad in scope, socially desirable, and ethically sound. They appeal to a variety of constituencies: those seeking to eliminate discrimination against women and improve the lives of children, as well as those seeking to reduce fertility and population growth. Mutually reinforcing investments in family planning, reproductive health, and a range of socioeconomic measures operate beneficially at both the macro and micro levels to slow population growth, increase productivity, and improve individual health and welfare.